Perubahan Struktur dan Kondisi Sosial-Ekonomi Masyarakat Pesisir Makassar Pasca Pembangunan Centre Point of Indonesia (CPI) - Annisa, Andi Andini Nurul; Natasya, Nur; Suciwarti, Suciwarti; Sadriani, Andi (Lembaga Yasin AlSys, 2024)
The development of Center Point Indonesia (CPI) in Makassar City, South Sulawesi has brought significant socio-economic changes to coastal communities. This study investigates changes in the structure and socio-economic situation of Makassar coastal communities with the development of the CPI. The research results show that this development affects the state of the coastal economy, reducing the income of shipping and fishing companies. This change has an impact on the employment situation in coastal areas, which previously was mostly involved in shipping and fishing. Many people are now thinking about looking for another job. The development of CPI has also changed the physical composition and size of coastal communities, which previously were only limited to the sea, are now larger and connected to other areas. This research uses qualitative research methods and collects data from secondary sources such as reports and articles regarding developments in the consumer price index and the situation of coastal communities in Makassar City. The results show that the evolution of the consumer price index has influenced the socio-economic conditions of coastal areas, which previously were mostly involved in shipping and fishing. Many people are now considering looking for another job. This development has also changed the physical composition and size of coastal communities, which were previously only limited to the sea, but are now increasingly spread out and connected to other areas.